Corporate Governance Frequently Asked Questions - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
This guidebook is designed to address common questionson corporate governance that are frequently asked byowners and managers of companies in the Middle Eastand North Africa (MENA) region. It familiarizes readerswith the basic concepts of corporate governance,providing a comprehensive overview of the subject matter,using case studies as practical examples of corporategovernance application in a commercial context. Overall,it demonstrates the value of corporate governance forbusinesses and for the region as a whole.The guidebook is designed to either be read in its entirety,as a complete work, or in sections, according to thereader’s interest. For ease of reference, the guidebookis organized into the following eight sections: 1) Commitment to Corporate Governance; 2)Corporate Governance for Small- and Medium-SizedEnterprises; 3) Board of Directors’ Role and Composition; 4) Functioning of the Board of Directors; 5) Control Environment; 6) Shareholder Issues; 7)Disclosure Issues; 8) Corporate Governance for Family-Owned Businesses; The approach of the guidebook is to explain technicalconcepts using plain language to help the readerbecome familiar with concepts that may sound newand unusual but are, in fact, part of the way business iscommonly conducted, organized, and controlled. The listof questions presented is not exhaustive, but provides asimple introduction to corporate governance, which canhelp improve business practices and assist the reader inunderstanding complex corporate governance guidelines.